(untitled) (Eurasian Journal of Philology Science and Education, 2023)
The article analyzes the poetic features of the works of the national poet Zhambyl Zhabaev, a mythological analysis is carried out. One of the poets who left a significant legacy in the history of Kazakh literature with his poetic art is Zhambyl Zhabayev. The artistry of the poet’s work, patriotism in his poems are still studied in literary studies, folklore studies. However, the mythological motif in the poet’s work has not been fully revealed. Mythical images in the works of Zhambyl Zhabaev are distinguished by the richness of poetic colors, juxtaposition and metaphoricity, deepen the mythological consciousness of the people. Each image in his poems is a source of oral literature, a common interest born of a folk dream and fantasy. Therefore, it is necessary to study each of his works in depth, to attach importance to each phenomenon. Currently, the works of many scientists are devoted to the study of certain aspects of oral literature, the nature of mythical monuments. However, there is still no monographic study on the depiction of the motifs of mythical monuments in the works of Zhambyl. In the article, folk poetry is taken as the main source of Zhambyl Zhabayev’s creativity, the specific features of the poet in the continuation of the tradition are determined. The interest in mythical concepts in Kazakh oral literature is determined not only by the historicity of the tendencies of its formation, but also by the enormous influence on the spiritual development of national consciousness. In our opinion, the problem of identifying mythical images in the works of Zhambyl Zhabaev is an important topic for a detailed study of the cognitive nature of mythical images of each century. This determines the relevance of this work. Keywords: poem, myth, image, mythology, concept, literature, folklore, worldview, mythological consciousness